The comparison of subjective image quality in conventional and digital panoramic radiography - Peker Ilkay; Toraman Alkurt; Usalan G; Altunkaynak B (Wolters Kluwer Medknow Publications, 2009)
Objective: The purpose of this study was to compare the subjective image quality of (1) regular intensifying screens with medium intensifying screens, (2) regular intensifying screens with digital radiography, and (3) medium intensifying screens with digital radiography for panoramic radiographs. Materials and Methods: Forty-five patients participated and a total of 90 radiographs were obtained in the study. The patients were divided into three groups (regular-medium intensifying screen, regular intensifying screen-digital radiography, and medium intensifying screen-digital radiography) that consisted of 15 people each. All radiographs were assessed by three oral radiologists independently. The observers evaluated the images using a 3-point scale (1=well visible, 0=partly visible, -1=not or hardly visible) for anatomical structures and pathological findings that are commonly found on panoramic radiographs. Subjective image quality of the groups and comparison of the observers were assessed by using non parametric Kruskal Wallis and Mann-Whitney U tests. Results: For all groups and observers, no statistically significant difference (p>0.05) was found for both anatomical structures and pathologies and between anatomical structures and pathologies according to the Mann Whitney U test. In comparison with observers, no statistically significant difference (p>0.05) was found for both anatomical structures and pathologies and between anatomical structures and pathologies for all groups according to the Kruskal Wallis test. Conclusion: The subjective image quality of medium and regular intensifying screens and conventional and digital panoramic radiographs were found statistically equal in this study.